The Ottoman Parliament Discussions for the Italian occupation of Libya (1911-1912) Between Democracy and Dictatorship (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
After the Committee of Union and Progress (CUP) Revolution of 1908 and the successful reintroduction of the Ottoman Constitution of 1876, the Unionists began to hold parliamentary elections, which were held in accordance with the electoral law issued by the Parliament in 1877 within the first constitutional experiment in the Ottoman Empire 1876-1878, and was restored Published on September 20, 1908. After the elections the Unionists were able to settle it in their favor by winning the majority of seats in the Parliament in its first legislative session in 1908-1912.The Parliament began its sessions on December 17, 1908 at a difficult time in the history of the Ottoman Empire internally and externally. One of the most important things faced by the Ottoman Empire was the Italian invasion on Libya, which began on September 29, 1911. The issue dominated the discussions of the Parliament as soon as its sessions resumed on October 14, 1911. Tripoli deputies put the issue for discussing in a manner consistent with the scale of the event, demanding that the Ottoman ministry be tried for treason for wasting an important part of the state's territory. The deputies in the Parliament interacted, in general, with this demand and accused the government of negligence and failure to provide the requirements to defend Libya. The subject of the invasion Italy over Libya dominated on the remainder of the first legislative session and extended even to the second legislative session, which opened in April 1912.Through this paper, we are trying to find out the nature of the discussions in the Parliament regarding the Italian occupation of Libya, Could the deputies speak freely and present their ideas as they want? What is the position of the Arab deputies? Who was the one who had the highest word in the Ottoman decision? the Parliament or the Government? And other questions that help to come up with a vision of whether the Parliament was democratic or not.